2016
DOI: 10.1080/03007995.2016.1248911
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in patients with type 2 diabetes newly initiated on basal insulin in the US in a community setting: impact on treatment discontinuation and hospitalization

Abstract: Objective: To evaluate the impact of 6 month hypoglycemia on treatment discontinuation and hospitalization of patients initiating basal insulin for type 2 diabetes (T2D) in real-world practice. Methods: This was a retrospective cohort study of patient-level data using electronic medical records (EMRs) in the Predictive Health Intelligence diabetes dataset. Data from adult patients with T2D initiating basal insulin glargine, insulin detemir, or Neutral Protamine Hagedorn insulin between January 2008 and March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…This study is the first to provide a nationally representative analysis of the Medicare‐insured population that examines the incidence of hypoglycaemia in new initiators of BI, factors associated with hypoglycaemia, and the association between early hypoglycaemia and patient adherence to and persistence with treatment. Our findings are consistent with a recent electronic medical record data analysis showing that patients with type 2 diabetes who have hypoglycaemia that occurs within the first 6 months after initiating BI were at an increased risk of discontinuing insulin compared with those who did not experience early hypoglycaemia . We found that early hypoglycaemia occurred in 9.1% of Medicare patients with type 2 diabetes who initiated BI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study is the first to provide a nationally representative analysis of the Medicare‐insured population that examines the incidence of hypoglycaemia in new initiators of BI, factors associated with hypoglycaemia, and the association between early hypoglycaemia and patient adherence to and persistence with treatment. Our findings are consistent with a recent electronic medical record data analysis showing that patients with type 2 diabetes who have hypoglycaemia that occurs within the first 6 months after initiating BI were at an increased risk of discontinuing insulin compared with those who did not experience early hypoglycaemia . We found that early hypoglycaemia occurred in 9.1% of Medicare patients with type 2 diabetes who initiated BI.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with a recent electronic medical record data analysis showing that patients with type 2 diabetes who have hypoglycaemia that occurs within the first 6 months after initiating BI were at an increased risk of discontinuing insulin compared with those who did not experience early hypoglycaemia. 15 We found that early hypoglycaemia occurred in 9.1% of Medicare patients with type 2 diabetes who initiated BI. The real rate of hypoglycaemia is probably even higher as hypoglycaemia events that were not captured in claims data were not included, with the result that the incidence of hypoglycaemia is underreported.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Both the BEGIN and SWITCH 2 studies reported significantly reduced hypoglycaemia in patients randomized to IDeg vs Gla‐100, and the DEVOTE trial also reported less adjudicated severe hypoglycaemia in patients using IDeg vs Gla‐100 in a longer 2‐year follow‐up . This reduced risk of hypoglycaemia with the second‐generation basal insulin analogues may help reduce barriers for basal insulin use, improve adherence, and reduce hypoglycaemia‐related healthcare resource utilization and associated costs; further studies could provide evidence related to these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Not surprisingly, hypoglycaemia has been associated with increased healthcare resource utilization and hospitalizations. 6 Additionally, among older adults with T2D, hypoglycaemia has been associated with cognitive decline, dementia, falls, accidents and fractures. [7][8][9][10] Therefore, the American Diabetes Association recommends that treatments for older adults with T2D should focus on minimizing the risk of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%